2001
DOI: 10.1097/00003727-200107000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study of Strategies for Effective Weight Management in Type 2 Diabetes: Pounds Off with Empowerment (POWER)

Abstract: This pilot test effort focused on weight management strategies for individuals with type 2 diabetes living in rural, medically under-served communities. Randomly selected patients from the diabetes registry of a federally funded primary care practice in a rural community were randomized to one of two 8-week interventions: intensive lifestyle (reduced fat and calorie intake and increased activity) or intensive lifestyle plus ongoing formal evaluation for continuous quality improvement. Mean weight loss was 1.15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 19 publications
1
25
0
Order By: Relevance
“…While providing an excellent demonstration of prevention of type 2 diabetes, most of these studies used resource-intensive, individualized nutrition and exercise counseling that was based predominately in academic centers. Results from other studies have begun to provide evidence that community-based nutrition and exercise interventions can significantly reduce risk factors for diabetic complications (21)(22)(23). The levels of improvement found in these other studies are similar to those found in our study.…”
Section: Discussionsupporting
confidence: 88%
“…While providing an excellent demonstration of prevention of type 2 diabetes, most of these studies used resource-intensive, individualized nutrition and exercise counseling that was based predominately in academic centers. Results from other studies have begun to provide evidence that community-based nutrition and exercise interventions can significantly reduce risk factors for diabetic complications (21)(22)(23). The levels of improvement found in these other studies are similar to those found in our study.…”
Section: Discussionsupporting
confidence: 88%
“…Twenty-two interventions (71%) targeted patients (2024,26,27,29,30,32,3537,39,40,42,4447,50,51), five (16%) targeted the health care system (31,34,41,43,48,49), and four (13%) (25,28,33,38) were multifaceted, addressing both patients and the health care system. The length of the interventions ranged from 1 to 60 months (median 6 months), and the number of participants varied between 23 and 16,140, with a median of 170 participants.…”
Section: Resultsmentioning
confidence: 99%
“…102 The Insulin Resistance Atherosclerosis Study reported that increased participation in non-vigorous as well as overall and vigorous physical activity was associated with increased insulin sensitivity. 103 Improvements in insulin sensitivity and glucose tolerance are seen in sedentary individuals who incorporate moderate levels of activity into their lifestyle but the change appears to occur far more slowly and less dramatically compared with higher-intensity activity. 104 In a 10-year cohort study Finnish women who engaged in vigorous activity [a metabolic equivalent of task (MET) value of ≥ 6] less than once a week were found to have a greater age-adjusted risk of diabetes of 2.23 (95% CI 0.95 to 5.23; p = 0.043) than women who engaged in vigorous activity at least once a week.…”
Section: Intensitymentioning
confidence: 99%